PEMANFAATAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS X MULTIMEDIA PADA MATA PELAJARAN KOMPUTER DAN JARINGAN DASAR DI SMK KETINTANG SURABAYA - Fadya Ayu Noviyanti; Utari Dewi (Educational Technology Journal, 2023)
This study aims to evaluate the effectiveness of cooperative learning model type make a match in improving the learning outcomes of students in class X Multimedia at SMK Ketintang Surabaya in basic computer and network subjects. The research was conducted with experimental method and used Nonequivalent Control Group Design. The research subjects consisted of two classes, namely the control class and the experimental class. The experimental class applied the make a match type cooperative learning model, while the control class applied conventional learning. The research data were collected through observation sheets and learning outcome tests. The results showed that the cooperative learning model of make a match type could be implemented well by teachers and students. The normality test results showed that the data were normally distributed and the homogeneity test results showed that the data were homogeneous. In addition, the results of hypothesis testing showed that there was a significant increase in the learning outcomes of students who applied the make a match type cooperative learning model compared to students who applied conventional learning. This research shows that the cooperative learning model of make a match type is effective in improving student learning outcomes in basic computer and network subjects at SMK Ketintang Surabaya. This learning model can be an alternative for teachers and schools in developing more effective and innovative learning strategies.